2004
DOI: 10.4049/jimmunol.172.5.2834
|View full text |Cite
|
Sign up to set email alerts
|

CD4 T Cell-Dependent CD8 T Cell Maturation

Abstract: We have investigated the contribution of CD4 T cells to the optimal priming of functionally robust memory CD8 T cell subsets. Intranasal infection of CD4 T cell-deficient (CD4−/−) mice with lymphocytic choriomeningitis virus resulted in the elaboration of virus-specific CD8 T cell responses that cleared the infection. However, by comparison with normal mice, the virus-specific CD8 T cells in CD4−/− mice were quantitatively and qualitatively different. In normal mice, lymphocytic choriomeningitis virus-specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
91
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(96 citation statements)
references
References 53 publications
5
91
0
Order By: Relevance
“…It is well documented that CD4 help is required for the generation of stable and protective CD8 memory, [30][31][32][33][34][35] whereas it is less crucial during the primary expansion phase of CD8 cells. Cytokines secreted by CD4 cells become involved in this process by promoting proliferation and survival of memory cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well documented that CD4 help is required for the generation of stable and protective CD8 memory, [30][31][32][33][34][35] whereas it is less crucial during the primary expansion phase of CD8 cells. Cytokines secreted by CD4 cells become involved in this process by promoting proliferation and survival of memory cells.…”
Section: Discussionmentioning
confidence: 99%
“…Cytokines secreted by CD4 cells become involved in this process by promoting proliferation and survival of memory cells. [32][33][34] In particular, an important role seems to be played by IL-2, which is largely produced by the CD4 T cell subset, is required for sustained expansion of CD8 T cells, and is directly associated with the expression of CD127 and the acquisition of a memory phenotype. 36 Furthermore, recent studies indicate that the absence of adequate CD4ϩ T cell help in the acute phase of infection can lead to the emergence of viral escape mutations in class I major histocompatibility complex-restricted epitopes and failure to resolve HCV infection.…”
Section: Discussionmentioning
confidence: 99%
“…CD4 ϩ T cell help is important for establishing effective CD8 ϩ memory T cell protection (50)(51)(52)(53), and the size of the memory T cell pool depends on the strength of the antigen stimulation (54)(55)(56). Initial levels of antigen produced by the single round of SIN-H particle infection may have been limiting and may not have fully engaged the available H-specific CD4 ϩ and CD8 ϩ T cells.…”
Section: Discussionmentioning
confidence: 99%
“…We also described that CD40-mediated signals on CD8 T cells were fundamental, observing that CD40-deficient CD8 T cells could not receive helper signals from CD4 T cells and were unable to differentiate into memory cells even in the presence of CD4 help (3). Beside the CD40/CD40L interaction, many other mechanisms of CD4 help have been described including other members of the TNF/ TNFR family (8,9), IL-2/IL-2R interactions (10,11), promotion of bystander survival for CD8 T cells (12), resistance to apoptosis (8), changes in effector and central memory T cell generation (13)(14)(15)(16), and differential expression of transcriptional factors (17). It has also been shown that CD4 T cells by taking up class I-peptide fragments from APCs could directly interact with CD8 T cells (18).…”
mentioning
confidence: 99%